The Tax System in India : Could Reform Spur Growth? - Poirson, Helene (Washington, D.C. : International Monetary Fund, 2006)
This paper assesses the effects of India's tax system on growth, through the level and productivity of private investment. Comparison of India's indicators of effective tax rates and tax revenue productivity with other countries shows that the Indian tax system is characterized by: (1) a high dependence on indirect taxes, (2) low average effective tax rates and tax productivity, and (3) high marginal effective tax rates and large tax-induced distortions on investment and financing decisions. The paper finds that the most recently proposed package of reforms would improve tax productivity and lower the marginal tax burden and tax-induced distortions. But firms that rely on internal sources of funds or face problems borrowing would continue to face high marginal tax rates.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet